Unprecedented Strong Panchromic Absorption from Proton‐Switchable Iridium(III) Azoimidazolate Complexes. Issue 52 (16th November 2015) - Henwood, Adam F.; Hu, Yue; Sajjad, Muhammad T.; K. V. V. Thalluri, Gopala; Ghosh, Sanjay S.; Cordes, David B.; Slawin, Alexandra M. Z.; Samuel, Ifor D. W.; Robertson, Neil; Zysman‐Colman, Eli
Abstract: Two new heteroleptic iridium(III) complexes bearing an aryldiazoimidazole ligand are reported. These complexes differ structurally with respect to the protonation state of the imidazole ring, but can be independently accessed by varying the synthetic conditions. Their structures have been unequivocally confirmed by X‐ray crystal structure analysis, with surprising differences in the structural parameters of the two complexes. The strongly absorbing nature of the free diazoimidazole ligand is enhanced in these iridium complexes, with the protonated cationic complex demonstrating extraordinarily strong panchromic absorption up to 700 nm. The absorption profile of the deprotonated neutral complex is blueshifted by about 100 nm and thus the interconversion between the two complexes as a function of the acidity/basicity of the environment can be readily monitored by absorption spectroscopy. Theoretical calculations revealed the origins of these markedly different absorption properties. Finally, the protonated analogue has been targeted as an acceptor material for organic photovoltaic (OPV) applications, and preliminary results are reported. Abstract : Organic photovoltaic applications : Two new iridium complexes containing azoimidazole/imidazolate ligands were synthesized, and their photophysical properties were studied. Both complexes are strongly absorptive, demonstrating absorption up to 700 nm, with very high molar extinction coefficients at long wavelengths (see scheme).